2000
DOI: 10.1002/(sici)1097-4628(20000509)76:6<868::aid-app13>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure-property relationships of lightly chemical crosslinked poly(vinyl chloride) thermoplastic elastomer

Abstract: Chemical crosslinked poly(vinyl chloride) (C-PVC) was synthesized by vinyl chloride suspension polymerization in the presence of diallyl phthalate (DAP) and plasticized to prepare poly(vinyl chloride) (PVC) thermoplastic elastomer (TPE) materials. The chemical crosslinking and physical crosslinking structure in chemical crosslinked PVC-TPE were investigated. It showed that the gel fraction and the crosslinking density of gel increased as the feed concentration of DAP increased. C-PVC prepared by VC/DAP copolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Figure shows DSC thermograms for the COP45 block copolymer sample, its gel fraction, and a PVC reference sample (S950). In agreement with the findings of Bao et al , the results obtained for lightly crosslinked PVC products, from materials analyzed as a whole, show differences that are due to the presence of crystallites that cannot be easily detected in the DSC profile. Fractionation of the block copolymer allows separation of the gel fraction to take place.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure shows DSC thermograms for the COP45 block copolymer sample, its gel fraction, and a PVC reference sample (S950). In agreement with the findings of Bao et al , the results obtained for lightly crosslinked PVC products, from materials analyzed as a whole, show differences that are due to the presence of crystallites that cannot be easily detected in the DSC profile. Fractionation of the block copolymer allows separation of the gel fraction to take place.…”
Section: Resultssupporting
confidence: 91%
“…The presence of a crosslinked fraction in PVC can be identified by determining its gel fraction . The synthesized PVC‐b‐PHPA‐b‐PVC block copolymers had a fraction insoluble in THF.…”
Section: Resultsmentioning
confidence: 99%
“…Distinct advantages arising from PVC plasticization are low cost, versatile processing of various shapes and designs [23], which make soft PVC the main alternative to replace flexible products based on elastomers or leather. The main limitations in the application of soft PVC come from its poor thermal and chemical resistance properties [24,25]. Crosslinking soft PVC by using a crosslinking agent is the most effective way to improve thermal and transport properties of flexible PVC.…”
Section: Methodsmentioning
confidence: 99%
“…There is also some research about the crosslinked PVC polymerization. Recently, Bao et al and Luo et al8–12 have shown an active investigation about crosslinking of PVC during polymerization reaction and published a series of articles about their results. Those results were invaluable especially in that they set up the detailed theoretical background about the crosslinked PVC polymerization which had remained out of researchers' interest for so long.…”
Section: Introductionmentioning
confidence: 99%